2009
DOI: 10.1002/aqc.1030
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of killer whales in Scottish inshore waters: temporal and spatial patterns relative to the distribution of declining harbour seal populations

Abstract: 2. There was a strong seasonal peak in sightings around Shetland during June-July, coinciding with the harbour seal pupping season. 5. These findings are discussed in terms of potential impacts upon local declining harbour seal populations and future research requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…A similar decline has been observed in Scottish waters: harbour seals Phoca vitulina in Shetland and Orkney declined by 40% between 2000 and 2006 (Lonergan et al 2007). Harbour seals are a preferred prey of killer whales in the northeastern Pacific (Ford et al 1998, Saulitis et al 2000, Dahlheim & White 2010, and predation on harbour seals has also been reported from killer whales around Shetland and Orkney (Weir 2002, Bolt et al 2009). …”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…A similar decline has been observed in Scottish waters: harbour seals Phoca vitulina in Shetland and Orkney declined by 40% between 2000 and 2006 (Lonergan et al 2007). Harbour seals are a preferred prey of killer whales in the northeastern Pacific (Ford et al 1998, Saulitis et al 2000, Dahlheim & White 2010, and predation on harbour seals has also been reported from killer whales around Shetland and Orkney (Weir 2002, Bolt et al 2009). …”
Section: Introductionmentioning
confidence: 58%
“…While predation by killer whales could be an important factor in the decline in harbour seals off northern Scotland (Bolt et al 2009), assessing the impact of killer whale predation requires precise information on abundance, distribution, diet and population identity of local killer whales. Killer whales have been sighted regularly in Shetland waters since the 1970s (Evans 1988, Weir 2002.…”
Section: Introductionmentioning
confidence: 99%
“…As above, there is likely to be a seasonal bias in opportunistic encounters. The occurrence of killer whales in this area is highly correlated with the harbor seal pupping season (Bolt et al 2009) and observed predation events, group follows and collected prey remains suggest that the killer whales photo-identified in this area are predating frequently upon seals (Foote unpublished data).…”
Section: Study Sites and Data Collectionmentioning
confidence: 93%
“…There are no published studies using data on identified individuals from any other region of the Northeast Atlantic. Therefore, although it is known that killer whales are regularly seen feeding around trawlers in the northern North Sea (Luque et al 2006), predating seals around the Northern Isles (Bolt et al 2009) and feeding on herring around Iceland (Simon et al 2007), we know nothing of the relationship among these groups of killer whales and movement among these sites.…”
Section: Introductionmentioning
confidence: 96%
“…Our study is the first successful application of a forensic DNA technique in the marine environment and could be extended to identify other marine aggressors (Bolt et al 2009, Estes et al 2009), including cases involving persons mutilated at sea (Sweet & Shutler 1999). Fig.…”
Section: Discussionmentioning
confidence: 96%